The effect of sentiment on institutional investors: A gender analysis - Monika Gehde-Trapp; Linda Klingler (University of Cologne, Centre for Financial Research (CFR), 2022)
In this paper, we explore whether male and female fund managers react differently to sentiment. Our main idea is that sentiment indicates mispricings of stocks relative to their fundamental values, and that rational fund managers should profit from these mispricings. As trading against the mispricing is risky, we hypothesize that female fund managers take on less aggressive positions. Indeed, our empirical results show that male fund managers hold portfolios with significantly higher total fund risk and unsystematic risk when sentiment is bad. For female fund managers, we find significantly lower levels in unsystematic risk when sentiment is bad. This difference in risk-taking behavior does not affect fund returns or risk-adjusted performance.
Keywords: G11; G23; G40; 330; mutual funds; gender; sentiment; investment behavior